Disaster Communication Campaign Via Instagram and Twitter Palang Merah Indonesia - Nur Muliasari; Vinka Audrina Sahrir; Nursaleh Hartaman (Jurnal Audiens, 2022)
This study aimed to find out the effect given by the campaign with determining the effect of "Palang Merah Indonesia" (PMI)'s social media content as the focus of this study using the theory of usability and effect. The research method used in this study uses qualitative method by using Nvivo application as a tool in this study. Palang Merah Indonesia (PMI) was one of the institutions that work in field of health and humanity. Support to the general public with more reach can be done on social media by campaigning. Disaster communication campaigns are a form of support to the general public through social media such as instagram and twitter. The results showed the majority of followers of PMI social media accounts were in the productive age group, and this community group, giving support to PMI is influenced by Twitter more dominantly than Instagram.